First-year-students' perceptions of asynchronous media platform (AMP) for learning English - Sunjayanto Masykuri, Edi; Vlаdimirоvnа, Vоrоnushkinа Olesya; Evgenevichc, Mezentsev Ivan (English Language Teaching Educational Journal, 2023)
This study investigates the attitudes of first-year university students toward the use of asynchronous applications in learning reading comprehension. The primary objectives were to determine students' perceptions of using smartphone-based asynchronous media platforms (AMP) for reading comprehension, assess how these applications enhance student engagement, and understand the rationale behind their use. Data were collected via a questionnaire administered to twenty-seven first-year university students. A case study approach was employed, and the data were analyzed using descriptive statistical methods. The findings indicate that students have a positive attitude toward the use of asynchronous applications for reading comprehension, with high average scores on the questionnaire demonstrating favorable assessments of these tools. The positive student attitudes toward asynchronous applications suggest that integrating these tools into the EFL curriculum could significantly enhance reading comprehension and engagement. The use of asynchronous media platforms provides flexibility and accessibility, enabling students to learn at their own pace and on their own schedule. In conclusion, the findings of this study highlight the potential benefits of asynchronous applications in EFL learning environments. By adopting these tools, educators can create more dynamic and interactive learning experiences that cater to the diverse needs of students.